2014
DOI: 10.4028/www.scientific.net/amr.898.225
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimal Design Roller of Y-Type Mill Using Ga Combined with FEM

Abstract: Y-Type rolling mill with three roller is a new kind of wire mill. Because of its unique advantage, It is very important to optimize structure. Roller is important part of the rolling mill, whose size effects the strength, stiffness, as well as the rolling piece quality and service life of the rolling mill. Therefore, It is important to optimize the roller structure dimension of Y-type mill.A new structure optimizing method is set up combined the modified genetic algorithms with finite element method.This metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Considering the asymmetric structure of the rolling mill system, Huang [19] established a chatter model by coupling a rolling process model and structure model to describe the asymmetric vibration characteristics, and found that the influence of the asymmetric structure parameters on the stability and critical conditions is noteworthy. In [20], Ma et al established a structural optimization method for a new Y-type rolling mill, which can solve the multiobjective problem of more complex constraints in engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the asymmetric structure of the rolling mill system, Huang [19] established a chatter model by coupling a rolling process model and structure model to describe the asymmetric vibration characteristics, and found that the influence of the asymmetric structure parameters on the stability and critical conditions is noteworthy. In [20], Ma et al established a structural optimization method for a new Y-type rolling mill, which can solve the multiobjective problem of more complex constraints in engineering.…”
Section: Introductionmentioning
confidence: 99%